Lipoproteins, not lipopolysaccharide, are the key mediators of the pro-inflammatory response elicited by heat-killed Brucella abortus. - Giambartolomei, Guillermo Hernan (2004)
Inflammation is a hallmark of brucellosis. Although Brucella abortus, one of the disease?s etiologic agents, possesses cytokine-stimulatory properties, the mechanism by which this bacterium triggers a proinflammatory response is not known. We examined the mechanism whereby heat-killed B. abortus (HKBA), as well as its LPS, induces production of inflammatory cytokines in monocytes/macrophages. Polymyxin B, a specific inhibitor of LPS activity, did not inhibit the production of TNF-- and IL-6-induced HKBA in the human monocytic cell line THP-1. HKBA induced the production of these cytokines in peritoneal macrophages of both C3H/HeJ and C3H/HeN mice, whereas B. abortus LPS only stimulated cells from C3H/HeN mice. Anti-TLR2 Ab, but not anti-TLR4 Ab, blocked HKBAmediated TNF-and IL-6 production in THP-1 cells. Because bacterial lipoproteins, a TLR2 ligand, have potent inherent stimulatory properties, we investigated the capacity of two B. abortus lipoproteins, outer membrane protein 19 (Omp19) and Omp16, to elicit a proinflammatory response. Lipidated (L)-Omp16 and L-Omp19, but not their unlipidated forms, induced the secretion of TNF-, IL-6, IL-10, and IL-12 in a time- and dose-dependent fashion. Preincubation of THP-1 cells with anti-TLR2 Ab blocked L-Omp19-mediated TNF-and IL-6 production. Together, these results entail a mechanism whereby B. abortus can stimulate cells from the innate immune system and induce cytokine-mediated inflammation in brucellosis. We submit that LPS is not the cause of inflammation in brucellosis; rather, lipoproteins of this organism trigger the production of proinflammatory cytokines, and TLR2 is involved in this process.